Preliminary results of "PASt21" - the Portuguese iniciative for performance assessment of water and wastewater treatment plants - Silva, C. (2011)
Performance assessment of water supply and wastewater services is nowadays a major issue. Over the past six years, LNEC has been developing performance assessment systems (PASs) for water treatment plants (WTPs) and wastewater treatment plants (WWTPs). In 2009, a national field test was launched, 'PASt21', coordinated by LNEC and involving 27 plants (10 WTP and 17 WWTP). This paper presents the second generation of the PI system for the overall performance assessment of WTPs and WWTPs and the PI results obtained with the data available for 2006-2009. It was concluded that all indicators of the systems are relevant, and the results show the ability of the proposed PI systems to assess the overall performance of a given treatment plant. The aggregated results are very important for the continuous improvement of the plant performance through benchmarking and targets’ periodic reassessment.